SISTEM INFORMASI KEUANGAN PADA UPTD GELANGGANG PEMUDA DAN OLAHRAGA DINAS SOSIAL, PEMUDA DAN OLAHRAGA KOTA SEMARANG BERBASIS CLIENT SERVER (Information Technology and Telematics, 2013)
Financial Information Systems at UPTD Gelanggang Pemuda dan Olahraga Dinas Sosial, Pemuda dan Olahraga Kota Semarang is the financial information system that works on computer network with client  server  based.  UPTD Gelanggang Pemuda dan Olahraga is a Technical Implementation Unit under  Dinas Sosial Pemuda dan Olahraga, which is engaged in the provision of sports infrastructure and youth facilities, such as: swimming pool, conference hall, youth hotels, tennis courts, badminton courts, football fields, athletic fields, office buildings and storefronts. UPTD Gelanggang Pemuda dan Olahraga are periodically required to report income earned and incurred operating expenses from funds of APBD Tk. II to the Dinas Sosial, Pemuda, dan Olahraga, Dinas Pengelola  Keuangan dan Aset Daerah, serta Inspektorat Wilayah Kota Semarang. The need for fast presentation of financial information, timely, relevant and trustworthy is certainly needed to support performance UPTD Gelanggang Pemuda dan Olahraga in particular in the determination  of target measures of income and other policy decisions. So with the implementation of financial  information systems client-sever based, it is expected an increase in the performance of UPTD Gelanggang Pemuda dan Olahraga Kota Semarang.Keywords: Financial Information System, Client Server.